2020
DOI: 10.25259/jcis_49_2020
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomic, Imaging, and Clinical Review of the Medial Longitudinal Fasciculus

Abstract: The medial longitudinal fasciculus (MLF) is a paired, highly specialized, and heavily myelinated nerve bundle responsible for extraocular muscle movements, including the oculomotor reflex, saccadic eye movements an smooth pursuit, and the vestibular ocular reflex. Clinically, lesions of the MLF are classically associated with internuclear ophthalmoplegia. However, clinical manifestations of a lesion in the MLF may be more complex and variable. We provide an overview of the neuroanatomy, neurologic manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…This phenomenon was compatible with internuclear ophthalmoplegia due to the lesion in the right MLF (MLF syndrome). The MLF is a paired, highly specialized, and heavily myelinated nerve bundle traveling in a craniocaudal direction near the midline within the tegmentum of the midbrain and dorsal pons [ 8 ]. In the midbrain, the MLF is located in the paramedian and lower portion [ 1 ], which is anatomically close to the CCN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon was compatible with internuclear ophthalmoplegia due to the lesion in the right MLF (MLF syndrome). The MLF is a paired, highly specialized, and heavily myelinated nerve bundle traveling in a craniocaudal direction near the midline within the tegmentum of the midbrain and dorsal pons [ 8 ]. In the midbrain, the MLF is located in the paramedian and lower portion [ 1 ], which is anatomically close to the CCN.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of midbrain infarctions have been attributed to atherothrombotic diseases of the large or small vessels [ 1 ]. The MLF in the dorsal tegmentum of the midbrain is supplied by small perforating branches of the P2 segment of the posterior cerebral artery [ 8 ]. In our patient, since no atrial fibrillation was observed, cardiogenic embolism did not seem to be involved in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…O fascículo longitudinal medial, situado pósterolateralmente à decussação das pirâmides, é deslocado posteriormente pela decussação sensitiva fazendo com que se estenda posteriormente ao lemnisco medial (Fiester et al, 2020). Ele mantém essa posição por toda extensão do bulbo.…”
Section: Fascículo Longitudinal Medialunclassified
“…Furthermore, it takes part in conjugate eye movements, including saccadic eye movements and smooth pursuit (Frohman et al, 2008 ). In addition, the MLF is essential for the vestibulo‐ocular reflex, which can stabilize the retinal images by producing eye movements compensatory for head movements (Nieuwenhuys et al, 1988 ), and the vestibular‐ocular fibers in the MLF are also in charge of coordination balance and linear acceleration through the semicircular and otolith‐mediated oculomotor reflex (Bae, Kim, Choi, Jung, & Kim, 2013 ; Fiester, Baig, Patel, & Rao, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The specific clinical signs produced by MLF injury can be divided into four distinct categories of disease based on the affected anatomy and function: (1) internuclear ophthalmoplegia (INO), (2) INO and trochlear syndrome, (3) INO and one‐and‐a‐half syndrome, and (4) wall‐eyed bilateral INO syndrome (Fiester et al, 2020 ). To investigate the correlation between MLF injury and clinical manifestations, diffusion tensor imaging (DTI) was used to evaluate the integrity of this fiber bundle through DTI metrics.…”
Section: Introductionmentioning
confidence: 99%